Effect of hard segment content on the phase separation and properties of hydroxyl-terminated polybutadiene thermoplastic polyurethane - Boxin Liu; Zhihao Niu; Zhanglei Wang; Yimin Wang; Hua Zou; Xiuying Zhao; Shikai Hu (Polymer Testing)
Thermoplastic polyurethane (TPU) possesses a distinctive microphase separation structure resulting from the thermodynamic incompatibility between its soft and hard segments. The content of hard segments is a significant factor that impacts the micromorphology and associated properties of TPU. In this study, hydroxyl-terminated polybutadiene thermoplastic polyurethanes (HTPB-TPUs) were synthesized using a two-step method in which hydroxyl-terminated polybutadiene, toluene diisocyanate, and 1,4-butanediol were incorporated. These HTPB-TPUs were designed to lack hydrogen bonding between the soft and hard segments. The structure and properties of the HTPB-TPUs were comprehensively evaluated. The results demonstrated a noticeable influence of the hard segment content on the degree of microphase separation. A combination of analytical techniques was employed to elucidate the effect of hard segment content on phase separation. Additionally, all-atom molecular dynamics simulations were conducted to determine the number of hydrogen bonds. These simulations served to verify the impact of the hard segment content on phase separation. Furthermore, the relationship between the hard segment content and the mechanical properties was elucidated by examining the phase separation phenomenon. This study provides valuable insights into the interaction between the structure and properties of TPU, laying a foundation for future investigations in this area.